A comparative study of suicidal and nonsuicidal self-injury characteristics in heterosexual versus sexual minority females. (March 2022) - Daurio, Allison M.; Ennis, Chelsea R.; Duffy, Mary E.; Taylor, Jeanette
Highlights: Women and sexual minorities are unduly impacted by self-harm and suicidality. Compared sexual minority and heterosexual women on self-harm and suicide features. Sexual minorities (versus heterosexuals) have stronger feelings of not belonging. Sexual minority women engage in more frequent self-harm than heterosexual women. These factors contribute to increased suicide attempts in sexual minority women. Abstract: Sexual minorities are at heightened risk for nonsuicidal self-injury (NSSI), suicidal ideation and attempts. We tested whether sexual minority and heterosexual females differ on these characteristics. Sexual minority females ( n  = 45) had higher lifetime frequency of NSSI and higher thwarted belonginess compared to heterosexual females ( n  = 47). These specific factors may contribute to the higher rates of suicide attempts among sexual minorities than heterosexual individuals.